The impact of witnessing cardiopulmonary resuscitation on nursing students: A review - Ratna Puji Priyanti; Iswanto; Siriluk Winitchayothin; Asri; Nurul Hidayah (UPPM STIKES Pemkab Jombang, 2025)
This review analyses the psychological effects of observing cardiopulmonary resuscitation (CPR) on nursing students, highlighting a significant disparity between technical training and emotional readiness within nursing education. Despite thorough procedural guidance, students often encounter anxiety, helplessness, and trauma during resuscitation events, especially in cases with unfavourable outcomes or the presence of distressed family members. Such experiences can elicit somatic symptoms, feelings of guilt, and enduring professional self-doubt. Challenges encompass gaps in knowledge regarding current CPR protocols, difficulties in interprofessional communication, and personal trauma histories that may exacerbate psychological distress. The result showed there are 3 themes: Psychological and emotional Impact; CPR performance and clinical competence; Students-teachers relationship. Educational interventions must focus on enhancing technical competence and psychological resilience through pre-exposure preparation, structured debriefing, and the integration of coping strategies. Nursing programs can enhance student wellbeing and improve clinical performance and patient outcomes by implementing a comprehensive approach to resuscitation education that recognises the multifaceted effects of these experiences.